2009
DOI: 10.1063/1.3125307
|View full text |Cite
|
Sign up to set email alerts
|

Frequency response of acoustic-assisted Ni–Mn–Ga ferromagnetic-shape-memory-alloy actuator

Abstract: A prototype of Ni-Mn-Ga based ferromagnetic-shape-memory-alloy (FSMA) actuator was designed and built; an acoustic-assist technique was applied to the actuator to enhance its performance. A piezoelectric stack actuator was attached to the Ni-MnGa sample to generate acoustic energy to enhance twin-boundary mobility and, hence, reduce the magnetic threshold field required for activating twin-boundary motion. The dynamic response of the acoustic-assist FSMA actuator was measured up to 1-kHz actuation. The acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 19 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…For instance, Heczko et al [18] showed that the shearing of the magnetization curve during the MFIS process is caused by the demagnetization field. Techapiesancharoenkij et al [19] pointed out that the switching field (onset of MFIS) and the saturating field (achievement of full MFIS), which determine the device volume and application possibility, depend on the sample shape and the loading conditions. On the other hand, a number of research works focused on the explanation and criterion of MFIS by proposing models without considering magnetic domains and domain walls [8,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Heczko et al [18] showed that the shearing of the magnetization curve during the MFIS process is caused by the demagnetization field. Techapiesancharoenkij et al [19] pointed out that the switching field (onset of MFIS) and the saturating field (achievement of full MFIS), which determine the device volume and application possibility, depend on the sample shape and the loading conditions. On the other hand, a number of research works focused on the explanation and criterion of MFIS by proposing models without considering magnetic domains and domain walls [8,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Further, they have been observed to exhibit twin boundary motion under magnetic actuation up to frequencies approaching 2 kHz [12]. It is likely, though not directly proven here, that twinboundary motion is responsible for the enhanced acoustic absorption reported here [13,14].…”
Section: Resultsmentioning
confidence: 95%
“…stresses) reduced from 2.8 MPa to 0.8 MPa. Due to the nonlinearity in the stress-strain relation of the martensite reorientation and the inertial effect in the high-frequency dynamic deformation (Henry, 2002;Lai et al, 2008;Pascan et al, 2016;Techapiesancharoenkij et al, 2011Techapiesancharoenkij et al, , 2009, the shape of the stress oscillation is different from that of the strain oscillation which is close to sinusoidal wave.…”
Section: Effect Of Long-time Actuationmentioning
confidence: 99%
“…Normally, the martensitic phase transformation of FSMA needs to be triggered by a high-level stress or a strong magnetic field, and is accompanied by large latent heat release/absorption that can be used as energy harvesters (Basaran, 2009;Saren et al, 2015;Sayyaadi et al, n.d.) and magneto-caloric refrigerators (Franco and Conde, 2012;Qu et al, 2017;Zhao et al, 2017). On the other hand, the martensite reorientation can be driven by a low stress (~1 MPa) or a weak magnetic field (< 1 Tesla) and has small hysteresis and energy dissipation, which are suitable for the applications such as actuators (Asua et al, 2014;Majewska et al, 2010;Smith et al, 2014;Techapiesancharoenkij et al, 2009;Yin et al, 2016) and sensors (Hobza et al, 2018;Sarawate and Dapino, 2006;Stephan et al, 2011;Yin et al, 2016). Particularly, there exists a special twin boundary (so-called Type II twin boundary) with ultra-low frictional twinning stress (~ 0.2 MPa) during the field-and/or stress-driven martensite reorientation in FSMA Ni-Mn-Ga single crystal, due to the monoclinic distortion of its 10M tetragonal martensite phase (although the deviation is small, e.g., the characteristic angle γ = 90.37° is close to 90 o of a tetragonal lattice) (Chulist et al, 2013;Heczko et al, 2013;Liu and Xie, 2003;Pascan et al, 2015;Sozinov et al, 2011;Straka et al, 2012Straka et al, , 2011bZou et al, 2017;Zreihan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%